A tecnologia da mesa educacional alfabeto A serviço da aquisição da leitura Na educação infantil - Nascimento, Maria do Socorro do (2015)
This research aims to assess to what extent information and communication technologies (ICT) contribute to the reading acquisition process. This work has as its core the implementation of an intervention project developed with children under five years of age, the Municipal Center for Child Education Mercia Maria Bezerra Costa, in Recife / PE, through the use of Educational Tables Alphabet, Positivo , computer company and educational technology. I have relied on Simonetti (2007) and Smith (2014), on the concepts of literacy and literacy; and Kenski (2012) and Ribeiro (2012), on the use of Digital Learning Objects, among others. For four weeks, students randomly chosen (twelve of the twenty-four class), attended by about sixty minutes daily classes in the multimedia room, living the practice of specific activities, and other remaining three hours of teaching time with mediation holder of the room teacher. This research was characterized as an action research, by allowing the intervention of the teacher within a social problem, mobilizing participants and giving opportunities for them to critically reflect on their actions in building new knowledge. The result shows that the earlier children have contact with the various genres, the greater the chances they like to read. The playful, present in educational digital games of Educational Tables alphabet, together with the methodology Different Paths, developed by Flower (2004), contributes significantly to learning, due mainly to the motivation and interaction provided by the artifact. The satisfactory result has become even more evident from the fact that the knowledge gained by the project members was higher than those who did not participate in the project. We refer to the high word in order that children who were in the classroom, without the intervention of the methodology and the use of educational table, remained, during the same period, without identifying letters and read words, while those They participated now have that power. Thus, the proposed objective was reached, to ensure learning for all involved in the research, and also to awaken, encourage and promote discussions on the use of these resources by the teacher. It was possible to achieve significant results regarding the acquisition of reading, in a pleasant way, but there needs to be planning the entire process, from clear and well-defined objectives, and not just to replace pencil and paper.